THE IMPACT OF UNIVERSITY APPROACHES TO TRAINING SPECIALISTS ON THEIR LEGAL STATUS (Journal of actual problems of jurisprudence, 2025)
This article examines the impact of various university approaches (Atlantic and continental) on the goals of training specialists in higher education institutions, and also discusses issues related to the legal status of universities. Important aspects are the autonomy of universities, student participation in management and financial independence, which are directly related to the legal status.The authors are of the opinion that the legal status of the university plays a key role in the formation of its functions, influencing the training of specialists, attracting teaching staff and ensuring the interests of students, employers and society as a whole.It is also noted that approaches to higher education taken from the Atlantic (Anglo-American) and continental (European) traditions can influence the structure of educational institutions and their functioning.The autonomy of universities and their financial independence, in particular, are highlighted as key elements that depend on the legal status and affect the ability of educational institutions to make decisions, form programs and ensure the quality of education.The research is aimed at studying the main goals of higher education institutions in the modern context, with a focus on training highly qualified specialists who meet the requirements of society and employers. The authors use various methods of analysis, including a comparative analysis of Atlantic (Anglo-American) and continental (European) approaches to training specialists at universities.Thus, the article focuses on the relationship between the legal status of universities and their educational functions, as well as on the impact of this relationship on various participants in the educational process and society as a whole.Keywords: law, higher education institution, legal status, specialties, university, university approaches.